Penyelesaian Wanprestasi dalam Perjanjian Kredit dengan Jaminan Fidusia Pada PT Reksa Finance di Kota Jakarta - Tiyas Asri Putri; Gunawan Djajaputra (UNES Law Review, 2023)
This research aims to examine the resolution of defaults in credit agreements with fiduciary guarantees at PT REKSA FINANCE in the City of Jakarta. Collateral in a credit agreement can be in the form of material collateral and personal collateral. Factors causing default involve debtor errors in managing their business, health problems that require medical costs, irregularities in the use of credit facilities, and bad faith in paying debts. PT REKSA FINANCE in Jakarta City is facing difficulties in returning loans that are not paid by debtors. This research underlines the need for PT REKSA FINANCE to focus more on non-litigation resolution in order to maintain its reputation and minimize default problems. Apart from that